Preoperative Plasma Club (Clara) Cell Secretory Protein Levels Are Associated With Primary Graft Dysfunction After Lung Transplantation. Issue 2 (8th January 2014) - Shah, R. J.; Wickersham, N.; Lederer, D. J.; Palmer, S. M.; Cantu, E.; Diamond, J. M.; Kawut, S. M.; Lama, V. N.; Bhorade, S.; Crespo, M.; Demissie, E.; Sonett, J.; et al.
Abstract Inherent recipient factors, including pretransplant diagnosis, obesity and elevated pulmonary pressures, are established primary graft dysfunction (PGD) risks. We evaluated the relationship between preoperative lung injury biomarkers and PGD to gain further mechanistic insight in recipients. We performed a prospective cohort study of recipients in the Lung Transplant Outcomes Group enrolled between 2002 and 2010. Our primary outcome was Grade 3 PGD on Day 2 or 3. We measured preoperative plasma levels of five biomarkers (CC‐16, sRAGE, ICAM‐1, IL‐8 and Protein C) that were previously associated with PGD when measured at the postoperative time point. We used multivariable logistic regression to adjust for potential confounders. Of 714 subjects, 130 (18%) developed PGD. Median CC‐16 levels were elevated in subjects with PGD (10.1 vs. 6.0, p < 0.001). CC‐16 was associated with PGD in nonidiopathic pulmonary fibrosis (non‐IPF) subjects (OR for highest quartile of CC‐16: 2.87, 95% CI: 1.37, 6.00, p = 0.005) but not in subjects with IPF (OR 1.38, 95% CI: 0.43, 4.45, p = 0.59). After adjustment, preoperative CC‐16 levels remained associated with PGD (OR: 3.03, 95% CI: 1.26, 7.30, p = 0.013) in non‐IPF subjects. Our study suggests the importance of preexisting airway epithelial injury in PGD. Markers of airway epithelial injury may be helpful in pretransplant risk stratification in specific recipients.